PEMBUATAN ALAT PERAGA MELALUI YOUTUBE MELALUI DISCOVERYLEARNING UNTUK MENGETAHUI HASIL BELAJAR PESERTA DIDIK - Febrianti, Rina Dewi; Sholihah, Fatikhatun Nikmatus (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to determine students' cognitive learning outcomes and products in the form of videos of making respiratory system props after applying discovery learning for class XI MIA at MA Nizhamiyah Ploso. This research is a type of pre-experimental research using the One Shot Case Study method. The subjects in this study were all students of class XI MIA MA Nizhamiyah ploso, totaling 14 students. The data collection techniques were observation, interviews, and questionnaires. while the data analysis is in the form of table diagrams. The results showed that in the learning outcomes there were students who got a value of 50, a value of 60, a value of 70, a value of 80, a value of 90. A total of 7 children were declared incomplete. While on the product results there are students who get a value of 75, a value of 79, a value of 83, a value of 88, a value of 91, a value of 96 and on the product results all students are declared complete